Concentrated DDAVP: Further Improvement in the Management of Mild Factor VIII Deficiencies - Ghirardini, A; Mariani, G; lacopino, G; Tirindelli, M C; Solinas, S; Moretti, T (Thrombosis and Haemostasis, 1987)
This study was carried out to evaluate the pharmacological efficacy of a new concentrated 1 Deamino - (8-D-arginine) - vasopressin (DDAVP) preparation. Concentrated DDAVP (C- DDAVP), (40 μg/mL) was given subcutaneously (s.c.) in hemophilia and von Willebrand Disease (vWD), and the response was evaluated in terms of factor VIII/vWF (VUI/von Willebrand Factor) complex response. This response was also compared to that obtained using the currently available commercial preparation (4 μg/mL) given either s.c. or intravenously (i. v.). The maximal f. VIII response after s.c. C-DDAVP was reached one hour after the injection (x:3.6 times the resting values) with an average decline of 15% at two hours. The response to s.c. C- DDAVP in patients with hemophilia was slightly better than thut obtained with the diluted brand, but the difference did not reach any statistical significance even when the schedules were compared in the same patients. In type I (placed normal subtype) vWD, a higher response in terms of factor VIII :C increase in comparison with hemophiliacs was obtained. Doth Ristocetin cofactor activity (RiCof) and bleeding time responded to this vasopressin analogue, when administered subcutaneously.
Keywords: DDAVP; Mild hemophilia; von Willebrand’s disease